(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
This article investigates the impact of peer feedback and collaboration on improving speaking proficiency in elementary school language classes. During the learning process, developing oral skills is crucial for students to effectively communicate in the target language. Traditional teaching methods often focus on teacher-led instruction, but incorporating peer feedback and collaboration can offer valuable opportunities for students to enhance their speaking skills. Collaboration in language classes exposes students to diverse perspectives and ideas, enriching their understanding and appreciation of different cultures and viewpoints